Characteristics of polyacrylonitrile pan-based polymer electrolytes for battery applications / Chong Woon Gie - Chong, Woon Gie (2013)

(untitled)
In the present study, three systems of polyacrylonitrile (PAN)-based polymer electrolytes samples were prepared. The first system is plasticized-PAN films containing different ratio of ethylene carbonate (EC) and dimethyl phthalate (DMP). The second system is salted-PAN films (PAN-LiBF4) and the third system is plasticized PAN films containing varying amounts of lithium tetrafluoroborate (PAN-EC-DMP-LiBF4). Pure PAN film was prepared as a reference. The room temperature conductivity for the highest conducting sample in the PAN-EC-DMP system, PAN-LiBF4 system and PAN-EC-DMP-LiBF4 system are 1.11 × 10-6 S cm-1, 1.83 × 10-3 S cm-1 and 1.08 × 10-2 S cm-1, respectively. The conductivity of the PAN-based polymer electrolyte has been found to be salt concentration dependent which is attributed to the increase in the number of mobile ions within the polymer matrix. The temperature dependence of conductivity for the films in PAN-LiBF4 system and PAN-EC-DMP-LiBF4 system from ambient temperature to 353 K obeys Arrhenius rule. The activation energies, Ea for these films were calculated to be in the range between 0.38 eV and 0.22 eV. The interactions of Li+ ions with nitrile groups of PAN in PAN-LiBF4 system and PAN-EC-DMP-LiBF4 system have been confirmed by Fourier Transform Infrared spectroscopy (FTIR). Differential Scanning Calorimetry (DSC) results have shown that both unplasticized and plasticized polymer electrolyte films were found to be thermally stable up to 200 °C. X-ray diffraction (XRD) results and glass transitions temperature studies have revealed that the crystalline region of PAN was effectively decreased upon addition of salt and plasticizers. The ionic and cationic transference numbers were evaluated by DC and combined DC and AC polarization methods to determine the charge carrier species within the polymer electrolyte films. The lithium ion conduction in the polymer electrolyte films is confirmed from Cyclic Voltammetry (CV) and transport number measurements. Linear sweep voltammetry (LSV) was employed to iv estimate the decomposition potential of the polymer electrolytes. The films were found to be electrochemically stable up to 4.4 V. A Li/LiCoO2 cell with the most electrochemically stable polymer electrolyte film has been fabricated and tested.